Aktywa niematerialne - kapitał wiedzy - wycena - Kwiecień, Mirosława (Intangible Assets - Capital of Knowledge - Valuation, 2007)
The author proved that the new challenge for both practice and theory of accounting is valuation and disclosure in financial statement, such assets as for example goodwill value, relations with clients etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 239-244